Local Heritage Values to Cope with Asia Future Shock In 2020 - Mulyaningsih Mulyaningsih (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2018)
A cultural and population changes have a biggest influence, the older Asian population, India became the second most influential country after the United States, the high investment costs, the lack of competence and competitiveness of Indonesian human resources as the second largest country after India resulted in the ASIA business situation and required Indonesia changed to become a country that counts in ASIA through the development of mindset and character based on local wisdom owned. The implementation of characteristic sharing organizational culture based on Pancasila philosophy and research based on local wisdom